Challenges and vision of wireless optical and acoustic communication in underwater environment. (21st May 2022) - Menaka, Deivasigamani; Gauni, Sabitha; Manimegalai, Chellapan Thangappan; Kalimuthu, Krishnan
Summary: Underwater Wireless Communication is a rapidly growing technology in the research domain. The researchers have been working towards the developments in underwater communication by investigating climatic changes, prediction of natural disasters, marine environment, monitoring aquatic life, oceanographic transmission, and data collection. The main objective of underwater communication is to achieve lossless, high transmission with the least power consumption. The Unmanned Underwater Vehicles (UUVs) and Autonomous Underwater Vehicles (AUVs) are set up with remote instruments and sensors to enable the natural exploration of the resources in the undersea environment. This research article is based on the study of various modes of communication, architectures, and protocol layers involved in underwater communication. Furthermore, an underwater hybrid connection is established by opto‐acoustic signals, and the overview of various performance characteristics, channel behaviors, and issues in the underwater scenario are investigated. Abstract : A vision about underwater wireless optical and acoustic communication in underwater environment is discussed with its real‐time existing applications. The existing optical and acoustic approaches with its novelty, various modes of communication, its 2D and 3D architectures with the protocol layers, and channel behaviors are analyzed. Challenges to achieve efficient underwater transmission are listed out. The simulation is performed to compare the optical and acoustic behaviors in terms of temperature, salinity, pressure, and depth velocity variations in underwater environment.